Cellular inhibitor of apoptosis‐2 is a critical regulator of apoptosis in airway epithelial cells treated with asthma‐related inflammatory cytokines. Issue 5 (11th October 2013) - Roscioli, Eugene; Hamon, Rhys; Ruffin, Richard E.; Lester, Susan; Zalewski, Peter
Abstract: Aberrant apoptosis of airway epithelial cells (AECs) is a disease contributing feature in the airways of asthmatics. The proinflammatory cytokines tumor necrosis factor α (TNFα) and interferon γ (IFNγ) are increased in asthma and have been shown to contribute to apoptosis at the airways. In the present study, we investigated the role of the inhibitor of apoptosis protein (IAP) family in primary AECs exposed to TNFα and IFNγ. IAPs are potent regulators of caspase activity elicited by the intrinsic and extrinsic apoptosis pathways. However, while caspase‐mediated apoptosis was observed in AECs exposed to doxorubicin, it was not observed after cytokine treatment. Instead, AECs exhibited proapoptotic changes evidenced by an increased Bax : Bcl2 transcript ratio and partial processing of procaspase‐3. Examination by quantitative reverse transcription polymerase chain reaction (qRT‐PCR) and Western analysis showed that proapoptotic changes were associated with a time‐ and dose‐dependent induction of cellular IAP‐2 (cIAP2), potentiated primarily by IFNγ. The abundance of the IAP antagonists X‐linked IAP‐associated factor 1 (XAF1) and second mitochondria‐derived activator of caspases did not change, although a moderate nuclear redistribution was observed for XAF1, which was also observed for cIAP2. Small interfering RNA (siRNA)‐mediated depletion of cIAP2 from AECs leads to caspase‐3 activation and poly (ADP‐ribose) polymerase cleavage, but this required extended cytokine exposure to produce a concomitant decrease in cIAP1 and Bcl2. These results indicate that AECs possess endogenous mechanisms making them highly resistant to apoptosis due to asthma‐related inflammatory cytokines, and the activity of cIAP2 plays an important role in this protection. Abstract : e00123 Abstract : Aberrant apoptosis in airway epithelial cells (AECs) is a common feature of asthma which contributes to pathology. The inhibitor of apoptosis proteins (IAPs) were examined for their role in aberrant apoptosis of AECs, in an in vitro model of inflammation. The cellular IAP was found to be critical in the prevention of apoptosis, as a result of asthma‐related proinflammatory cytokines.